The Maize Divergent spindle-1 (dv1) Gene Encodes a Kinesin-14A Motor Protein Required for Meiotic Spindle Pole Organization - Higgins, David M.; Nannas, Natalie J.; Dawe, R. Kelly (Frontiers in Plant Science, 2016)
The classic maize mutant divergent spindle-1 (dv1) causes failures in meiotic spindle assembly and a decrease in pollen viability. By analyzing two independent dv1 alleles we demonstrate that this phenotype is caused by mutations in a member of the kinesin-14A subfamily, a class of C-terminal, minus-end directed microtubule motors. Further analysis demonstrates that defects in early spindle assembly are rare, but that later stages of spindle organization promoting the formation of finely focused spindle poles are strongly dependent on Dv1. Anaphase is error-prone in dv1 lines but not severely so, and the majority of cells show normal chromosome segregation. Live-cell imaging of wild type and mutant plants carrying CFP-tagged β-tubulin confirm that meiosis in dv1 lines fails primarily at the pole-sharpening phase of spindle assembly. These data indicate that plant kinesin-14A proteins help to enforce bipolarity by focusing spindle poles and that this stage of spindle assembly is not required for transition through the spindle checkpoint but improves the accuracy of chromosome segregation.